Use of an online gaming tool, the Veterinary DialogueTrainer, for teaching clinical communication skills to bovine veterinary practitioners - Dorrestein, Linda; Jansen, Jolanda; Plagis, Tessa; Ritter, Caroline; Vertenten, Geert; Barkema, Herman W. (Frontiers in Veterinary Science, 2023)
Effective clinical communication is essential for bovine veterinary practitioners to establish and maintain positive client relationships. When applied properly in herd health consultancy, it increases client satisfaction and adherence to veterinary advice, and improves patient health and welfare. Although communication skills are often taught by providing feedback on simulated conversations, this has limitations, including time constraints, subjective assessments, and cost. The Veterinary DialogueTrainer (VDT) is an online serious game platform using 'digital role-play' with avatars, recently developed to enhance and assess learning outcomes, improve use of learned skills, and increase cost-effectiveness of communication training. The objective was to evaluate its suitability and applicability. Finnish (n=24) and Swedish (n=21) bovine veterinarians participated in communication training using VDT for training and assessment. Participants completed the provided scenario at least twice. After playing a bovine health communication simulation, participants received their scores and feedback on selected conversation options. VDT scores measured multiple aspects of communication on a 0-100% scale, based on motivational interviewing methodology and Calgary-Cambridge guidelines.Mean (±SD) number of attempts participants played the scenario was 4.1 (±2.6, Finland) and 3.9 (±1.3, Sweden), with highest total score reached after a mean of 3.5 (±2.1, Finland) and 3.1 (±1.1, Sweden) attempts. On the first attempt, 39 participants (87%) scored <50% of the highest possible score, whereas most (n=34, 76%) achieved a higher score on the second attempt. Mean total score increased from 15 (±14) to 77% (±33) for Finish participants and from 40 (±22.0) to 87% (±19.4) for Swedish participants. The majority (n= 33, 73%) of participants reached a score >80% after 4.0 (±1.6, Finland) or 2.8 (±1.0, Sweden) attempts.Net Promoter Score of the training was +89 (Finland), +88 (Finland) and +83 (Sweden) on a scale from -100 to +100, indicating most participants were very likely to recommend VDT to other veterinarians.The VDT increased communication skills scores but whether it will improve communication skills in practice requires further study. We concluded there is a likely benefit of using the VDT in teaching and monitoring veterinary communication competencies and preparing for offline role-plays and real-life conversations in veterinary practice.